2017
DOI: 10.1016/j.geoforum.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mediating the spaces of diet and health: A critical analysis of reporting on nutrition and colorectal cancer in the UK

Abstract: Citation: Wells, R. (2017). Mediating the spaces of diet and health: A critical analysis of reporting on nutrition and colorectal cancer in the UK. Geoforum, 84, pp. 228-238. doi: 10.1016Geoforum, 84, pp. 228-238. doi: 10. /j.geoforum.2016 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThe media are one of the main arenas in which nutrition information is framed and developed. Research has shown a predominantly individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…privileging certain voices over others. Wells (2017) found that the UK media coverage of nutritional means of preventing bowel cancer was primarily set in the "lifestyle" frame indicating that the responsibility for increasing dietary fibre was of the individual instead of discussions of structural drivers of dietary change such as social, economic or political drivers. In a more recent study, Yau et al (2021) found that the issue of food insecurity in the UK was predominantly covered by left-leaning and centrist newspapers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…privileging certain voices over others. Wells (2017) found that the UK media coverage of nutritional means of preventing bowel cancer was primarily set in the "lifestyle" frame indicating that the responsibility for increasing dietary fibre was of the individual instead of discussions of structural drivers of dietary change such as social, economic or political drivers. In a more recent study, Yau et al (2021) found that the issue of food insecurity in the UK was predominantly covered by left-leaning and centrist newspapers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, news values are not in line with the health information the population needs, particularly those considered underpriveleged (Epstein, 2008). Nutrition-related topics are covered according to lifestyle, placing a great amount of accountability on the individual, without taking into account social, economic, or political factors that can change one's diet (Wells, 2017). When the news provides solid recommendations for a healthy lifestyle, people are more likely to adopt this behavior (Chang, 2016).…”
Section: Introductionmentioning
confidence: 99%